Qingchang Wenzhong Decoction Alleviates DSS-Induced Inflammatory Bowel Disease by Inhibiting M1 Macrophage Polarization In Vitro and In Vivo. (25th August 2022) - Lu, Qiongqiong; Li, Junxiang; Ding, Panghua; Mao, Tangyou; Shi, Lei; Sun, Zhongmei; Tan, Xiang; Jiang, Hui; Dong, Junying; Li, Yalan; Yang, Xiaojun; Shi, Rui
Abstract : Background . An imbalance of macrophage M1/M2 polarization significantly influences the pathogenesis of inflammatory bowel disease. Qingchang Wenzhong decoction (QCWZD) has a proven therapeutic effect on patients with inflammatory bowel disease (IBD) and can significantly inhibit the inflammatory response in mice with colitis. However, its effect on macrophages during IBD treatment remains nebulous. Aim of the Study . Explore the mechanism underlying QCWZD effects in a dextran sulfate sodium (DSS)-induced colitis mouse model in vivo and RAW264.7 cell in vitro by observing macrophage polarization dynamics. Methods . The main active components of QCWZD were determined using high-performance liquid chromatography. Surface marker expression on M1-type macrophages was analyzed using flow cytometry and immunofluorescence. The effect on inducible nitric oxide synthase (iNOS), interleukin-6 (IL-6), and tumor necrosis factor- α (TNF- α ) released by M1 type macrophages was determined using ELSA and RT-PCR. The expression of key proteins in the JAK2/STAT3 signaling pathway was analyzed using western blotting. QCWZD cytotoxicity in macrophages was measured using CCK8 and Annexin V-FITC/PI assays. Results . The main active components of QCWZD were berberine chloride, coptisine chloride, epiberberine chloride, gallic acid, ginsenoside Rg1, ginsenoside Rb1, indigo, indirubin, notoginsenoside R1, palmatine chloride, and 6-curcumin. QCWZD markedly alleviated DSS-induced colitis in mice, as revealed by the rescued weight loss and disease activity index, attenuated the colonic shortening and mucosal injury associated with the inhibition of M1 macrophage polarization and expression of related cytokines, such as IL-6 and TNF- α, in vivo and in vitro . Furthermore, QCWZD decreased the iNOS, JAK2, and STAT3 levels in vivo and in vitro, regulating the JAK2/STAT3 signaling pathway. Conclusion . QCWZD administration improves intestinal inflammation by inhibiting M1 macrophage polarization. The JAK2/STAT3 signaling pathway may mediate the effects of QCWZD on M1 macrophage polarization in colitis treatment. This study presents a novel macrophage-mediated therapeutic strategy for the treatment of IBD.